Change in Taste in Diabetic Patients with Facial Nerve Palsy - Abd, Muataz Fairooz; Abbas, Ishraq Kadhim (AL-Kindy College Medical Journal, 2014)
Background: Bell's palsy was defined as facial weakness of lower motor neuron type caused by idiopathic facial nerve involvement outside the central nervous system without evidence of aural or more widespread neurologic disease. The cause is unclear, but the disorder occurs more commonly in diabetics.Objectives: to differentiate cases of idiopathic Bell's palsy from diabetic mononeuropathy presented with Facial nerve palsy by assessing the taste, because they differ in etiology, management & prognosis.Patients &Methods: One hundred and fifteen consecutive patients were referred for the treatment of facial palsy, from May the 5th 2012 to April 12th 2013 in Al-Kindy Teaching Hospital and The Neurosciences Hospital, in Baghdad / Iraq. 70 diabetic patients and 45 non diabetics were involved to assay the taste.RESULTS: of the 115 patients with facial nerve palsy 70 (61%) were diabetics&45(39%) non-diabetics.No differences of age or gender were found between the two groups. From those 70 diabetic patients 15(34.9%) had change in taste, and , 55(76.4%)had no change in taste, while for non-diabetics; from total 45 patients 28(65.1) had change in taste, and 17 (23.6%) had no change, and this was statistically significant (p